Understanding conformational dynamics of complex lipid mixtures relevant to biology - Friedman, Ran; Khalid, Syma; Aponte-Santamaria, Camilo; Arutyunova, Elena; Becker, Marlon; Boyd, Kevin J.; Christensen, Mikkel; Coimbra, Joao T. S.; Concilio, Simona; Daday, Csaba; van Eerden, Floris J.; Fernandes, Pedro A.; et al. (Journal of membrane biology, 2018)
This is a perspective article entitled "Frontiers in computational biophysics: understanding conformational dynamics of complex lipid mixtures relevant to biology" which is following a CECAM meeting with the same name.